(3MUGO GdbQf GdYQTQjf fSGA TgjQGJ (B:s (3GdLRA GdGhd (B/s - (3TGcQ, aDGOs ((3GdbGgQI (B:s (3GdOGQ GdeUQjI GddHfGfjI ,s, 2004)
(3GdcJGH GdPj Hjf jOjc YRjRj GdbGQF jYQV HGSdhH SdS h LPGH dfeGPL ef GdfSGA JSJMb cd hGMOI efgf Gf Jchf McGjI JQhi Gh QhGjI JMci de JcJSH TgQJgG ef aQGZ Gh HGdUOaI ef Hjfgf GdbdeGhj SgjQ(B- (3eGQi chQi(B- (3CLGJG cQjSJi(B- (3EfOjQ ZGfOj(B- (3gdf cdQ(B- (3LGcdjf cfjOj(B- (3gOi TYQGhjs
Keywords: (3CLGJG cQjSJis; (3EfOjQ ZGfOjs; (3eGQi chQis; (3GdbdeGhj SgjQs